Association between triglyceride-glucose index and clinical outcomes among patients with chronic kidney disease: a meta-analysis - Jinli Tuo; Zhong Li; Linshen Xie (BMC Nephrology)
Abstract Purpose To identify the relationship of triglyceride-glucose (TyG) index with clinical outcomes in chronic kidney disease (CKD) patients based on current available evidence. Methods PubMed, EMBASE, Web of Science and CNKI databases were searched up to August 31, 2024. Primary outcome was the all-cause mortality. Secondary outcomes included the coronary artery disease (CAD) mortality, CKD progression, risk of severe coronary artery stenosis (SCAS), major adverse cardiovascular event (MACE), coronary artery calcification (CAC) progression, end-stage renal disease (ESRD), and nonalcoholic fatty liver disease (NAFLD). The hazard ratio (HR) and odds ratio (OR) with 95% confidence interval (CI) were combined to assess the predictive role of TyG index for above clinical outcomes among CKD patients. All statistical analysis was performed by STATA 15.0 version. Results Twelve studies with 26,530 cases were included. Pooled results indicated that elevated TyG index was significantly related to increased risk for all-cause mortality (HR = 1.22, 95% CI: 1.13–1.31, P<0.001). Besides, high TyG index was also associated with the CAD mortality (HR = 1.19, 95% CI: 1.04–1.36, P = 0.011), occurrence of CKD progression (HR = 1.52, 95% CI: 1.36–1.70, P<0.001), SCAS (OR = 1.79, 95% CI: 1.13–2.83, P = 0.013), MACE (OR = 1.68, 95% CI: 1.11–2.54, P = 0.014), CAC progression (OR = 1.55, 95% CI: 1.06–1.76, P = 0.02), CAD (OR = 2.865, 95% CI: 1.681–4.885, P<0.001), ESRD (OR = 1.49, 95% CI: 1.12–1.99, P = 0.006) and NAFLD (OR = 4.903, 95% CI: 3.046–7.893, P<0.001). Conclusion High TyG index predicts poor clinical outcomes and might serve as a novel prognostic indicator among CKD patients. However, more studies are still needed to verify above findings.